2020
DOI: 10.3389/fnins.2020.00733
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Changes of Amplitude of Low-Frequency Fluctuations in Cervical Discogenic Pain

Abstract: Cervical discogenic pain (CDP) is a clinically common pain syndrome caused by cervical disk degeneration. A large number of studies have reported that CDP results in brain functional impairments. However, the detailed dynamic brain functional abnormalities in CDP are still unclear. In this study, using resting-state functional magnetic resonance imaging, we explored the neural basis of CDP with 40 CDP patients and 40 age-, gender-matched healthy controls to delineate the changes of the voxel-level static and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
2
11
0
Order By: Relevance
“…The decreased functional connectivities between the middle cingulate cortex and left posterior insula, and left postcentral gyrus were found in CDP patients. Our finding was supported by previous studies which found changed structures and functions in these areas in cervical spondylosis and chronic knee osteoarthritis ( Liao et al, 2018 ; Woodworth et al, 2019 ; Ma et al, 2020 ). The middle cingulate cortex has been reported in pain processing and is considered to be a key region in the pain matrix ( Peyron et al, 2000 ; Favilla et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The decreased functional connectivities between the middle cingulate cortex and left posterior insula, and left postcentral gyrus were found in CDP patients. Our finding was supported by previous studies which found changed structures and functions in these areas in cervical spondylosis and chronic knee osteoarthritis ( Liao et al, 2018 ; Woodworth et al, 2019 ; Ma et al, 2020 ). The middle cingulate cortex has been reported in pain processing and is considered to be a key region in the pain matrix ( Peyron et al, 2000 ; Favilla et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…A study using magnetic resonance imaging found that people with neuropathic pain showed reduced GABA in the thalamus ( Henderson et al, 2013 ). The abnormal static and dynamic amplitude of low frequency fluctuations in CDP were also found in our previous study ( Ma et al, 2020 ). All the evidence indicated that the abnormal functional activities or couplings of the insula and thalamus may be a neuromarker for CDP.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recently, using sliding-window approach, the dynamic ALFF (dALFF) method was developed by calculating the variance of ALFF over time (Fu et al, 2018 ). The dALFF has been applied to study the functional activity abnormalities in subjects under disease state and provides some new evidence (Fu et al, 2018 ; Ma et al, 2020 ; Pang et al, 2020 ). Thus, to reveal the dynamic changes of the low-frequency oscillation in migraine patients may provide supplementary information to understand its neural basis.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic local metrics analysis was performed using TDA toolkits based on RESTplus ( Jia et al, 2019 ) (see text footnote 1). The dynamic metrics was calculated using a sliding window method, and it is sensitive in detecting time-dependent variations and examining metrics variability over the whole brain ( Hindriks et al, 2016 ; Yan et al, 2017 ; Fu et al, 2018 ; Ma M. et al, 2020 ). The most important parameter in resting-state dynamic computation is window length.…”
Section: Methodsmentioning
confidence: 99%